2018
DOI: 10.1016/j.biocel.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ELF3 facilitates cell growth and metastasis through PI3K/Akt and ERK signaling pathways in non-small cell lung cancer

Abstract: ELF3 is one of the member of transcription factors from E-twenty-six family, its role varies in different types of cancer. However, the role and specific mechanisms of ELF3 in the development of non-small cell lung cancer (NSCLC) still remains largely unknown. In our study, ELF3 was observed to be upregulated in NSCLC tissues compared to the corresponding normal lung tissue at mRNA and protein levels, and its expression level was correlated with the overall survival of patients with NSCLC. Silencing of the ELF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 36 publications
1
58
0
Order By: Relevance
“…Targeted therapy is a new therapeutic paradigm to cure cancer by targeting specific and promising molecular targets. Recently, Wang et al reported that Elf3 (ESE-1) facilitates the growth and metastasis of lung cancer cells (19). We also explored the possibility of using ESE-1 as a molecular target for lung cancer in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…Targeted therapy is a new therapeutic paradigm to cure cancer by targeting specific and promising molecular targets. Recently, Wang et al reported that Elf3 (ESE-1) facilitates the growth and metastasis of lung cancer cells (19). We also explored the possibility of using ESE-1 as a molecular target for lung cancer in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we found that TSPY1 contributed to the upregulation of p‐RAF1, p‐MEK1/2, and p‐ERK1/2 in the RAS signaling pathway in both A549 and HepG2 cells and that the JUN protein level was consequently increased (Figures B and ). Considering the significance of PI3K/AKT/mTOR/BCL2 and RAS/RAF/MEK/ERK/JUN signaling pathways in cell proliferation, cycle, invasiveness, and apoptosis, we propose that TSPY1 affects cell biological phenotypes probably through a cross‐talk network that involves the molecules with functional regulation of both PI3K/AKT and RAS signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…C, Western blot analysis showed higher levels of 4 key proteins (p-RAF-1, p-MEK1/2, p-ERK1/2, and JUN) of the RAS signaling pathway in A549 and HepG2 cells with IGFBP3 knockdown, relative to controls (shNC and siNC) signaling pathways, and this promotion depended on the inhibition of TSPY1 on IGFBP3 expression. The PI3K/AKT and RAS signaling pathways are key signal transduction components in the regulation of cell growth, cell differentiation, cell cycle, apoptosis, and metastasis, [22][23][24][25][26] and recent reports show that deregulated activation of the 2 signalings is frequently observed in many cancers. [29][30][31] Therefore, our findings provided a potential common mechanism of TSPY1's function as an oncogene in the tumor process.…”
Section: Discussionmentioning
confidence: 99%
“…ESE-1 belongs to the ETS family of transcription factors and has been associated with cancer progression. 6,7 However, its observed effects are controversial 9,18,19,22,[24][25][26][27][28][29][30]32,40,41 ; whether ESE-1 is oncogenic or tumor suppressive has not been clearly determined in colon cancer or in any other type of cancer using an in vivo mouse model. Since inflammatory bowel disease (IBD)-related carcinogenesis is a very common pathological and clinical aspect of colon cancer, we adopted an AOM-induced and DSS-promoted colon cancer model using ESE-1 knockout mice, which may potentially be more susceptible to colonic inflammation and neoplasia.…”
Section: Discussionmentioning
confidence: 99%